A measure of the attitudes of faculty members at the Middle East University in Jordan towards electronic tests according to the method of Thurstone - Rahman Shatat, Khalida Abdul (Opción, 1970)
This study aimed at building a measure of the attitudes of faculty members at the University of the Middle East towards electronic tests, according to the Thurstone method for categories that appear to be equal. In order to achieve the objectives of the study, (30) items measuring attitudes toward electronic tests were presented to (15) arbitrators with expertise and specialization, in order to classify each item in terms of severity of preference or lack of preference for the topic of attitudes. The gradual values of the items were calculated, and (20) items were selected, distributed with equal dimensions of the gradual values. There were indications of validity and reliability of the measure.